The Stress and Adversity Inventory for Adults (Adult STRAIN) in Brazilian Portuguese: Initial Validation and Links With Executive Function, Sleep, and Mental and Physical Health - Cazassa, Milton J.; Oliveira, Margareth da S.; Spahr, Chandler M.; Shields, Grant S.; Slavich, George M. (Frontiers in Psychology, 2020)
It has been widely hypothesized that stressors occurring over the lifespan exert a cumulative impact on health, but little work has directly tested these theories given the difficulty associated with measuring cumulative stress exposure over the lifespan. We addressed this issue in Brazil by translating the Stress and Adversity Inventory for Adults (Adult STRAIN) into Brazilian Portuguese. We then examined the instrument’s usability and acceptability; concurrent, discriminant, predictive, and incremental validity; and test-retest reliability. Participants were 330 Brazilian adults (238 women; Mage = 32.16; range: 18-76 years old) who completed the Adult STRAIN in Brazilian Portuguese, Childhood Trauma Questionnaire-Short Form (CTQ-SF), and Perceived Stress Scale (PSS). They also completed measures of socioeconomic status, personality, social desirability, negative affect, physical and mental health complaints, sleep quality, executive function, and doctor-diagnosed general health problems and autoimmune disorders. The STRAIN exhibited excellent usability and acceptability and was completed in 16 minutes and 27 seconds, on average. It showed good concurrent validity relative to the CTQ-SF and PSS (r ≥ .377) and good discriminant validity, both with and without adjusting for covariates. In addition, the STRAIN significantly predicted all of the health outcomes assessed except for executive function and explained substantial variance in these outcomes over and above the CTQ-SF, PSS, and covariates assessed. Finally, the test-retest reliability indices for total lifetime stressor count and severity were outstanding (ricc = .936 and .953, respectively, over M = 34.86 days). The Adult STRAIN in Brazilian Portuguese thus exhibits excellent usability and acceptability, good concurrent and discriminant validity, strong predictive and incremental validity across a variety of health outcomes, and outstanding test-retest reliability. We therefore conclude that the STRAIN is a practical, valid, and reliable instrument for researchers and clinicians looking to efficiently assess cumulative lifetime stress exposure in Brazilian Portuguese.